Laju Korosi Pada Baja Karbon Sedang Akibat Proses Pencelupan Pada Larutan Asam Sulfat (H2SO4) dan Asam Klorida (HCl) dengan Waktu Bervariasi - Miduk Tampubolon; Roy Ganda Gultom; Lestina Siagian; Partahi Lumbangaol; Charles Manurung (SPROCKET JOURNAL OF MECHANICAL ENGINEERING, 2020)
An experiment has been conducted to determine corrosion rate of medium carbon stell with sulfuric acid solution, Aquades 90,2% + H2SO4 9,8% and hydrochloric acid solution, Aquades 96,8% + HCl 3,2%. By using weight loss method, if medium carbon steel dipped into sulfuric acid solution then the corrosion rate is faster than it dipped into hydrochloric solution. If medium carbon steel dipped in a long time than the corrosion rate slowing down.